The Relationship between Waiting Time and Patient Satisfaction in The Outpatient of Public Hospital in Banjarbaru - Ichsan Rizany; Herry Setiawan; Musafaah Musafaah; Herry Setiawan (Universitas Muhammadiyah Yogyakarta, 2021)
Background: Outpatients often complain about hospital services, one of which is waiting time. High complaints have an impact on patient satisfaction. Currently, in several outpatient rooms at the hospital, long queues and long waiting times frequently occur.Objective: This study aims to determine the correlation between waiting time and patient satisfaction at Public Hospital.Method: This study used a non-experimental approach with a cross-sectional design. Samples were 93 patients selected by using random sampling technique at the public hospital in Banjarbaru city. The instruments used were the patient satisfaction questionnaire and waiting time observation. Data were analyzed using the chi-square test.Results: The results showed that 35 (37.6%) patients felt the standard waiting time according to regulations from the ministry of health (60 minutes), while 55 (59.1%) patients were satisfied with the services provided. There was a significant relationship between waiting time and patient satisfaction (p-value = 0.021).Conclusion: It can be concluded that there is a relationship between waiting time and patient satisfaction. Hospitals can implement online registration and manage the arrival of doctors in outpatient care so that waiting times and patient satisfaction can be managed according to minimum service standards